Da’wah and Strengthening the Understanding of Religious Moderation at Islamic Universities - Aslati Aslati; Eko Saputra; Masduki Masduki; Dony Arung Triantoro; Silawati Silawati (Jurnal Dakwah Risalah, 2022)
Departing from previous studies, which found that colleges were one of the locus for sowing intolerant, extreme, and radical religious views, this article examines the strengthening of moderate religious beliefs at Islamic universities in Riau Province, Indonesia. By taking case studies at three universities, namely the State Islamic University of Sultan Syarif Kasim of Riau, State Islamic College of Bengkalis, and Hubbul Wathan Islamic College of Duri. This article finds that the strengthening of the notion of religious moderation at the Islamic tertiary level has been manifested in many policies such as outreach, involving lecturers in some training, including religious moderation material as one of the college entrance test criteria for new students, and making religious moderation the theme of Real Work Lectures for students. This finding shows that Islamic tertiary institutions are not passive towards exposure to intolerance and radicalism but instead take up resistance to many policies. At the same time, this becomes a new da'wah activity for tertiary institutions in Riau.